Efecto de fungicidas sistémicos sobre enfermedades asociadas al cultivo de arroz (Oryza sativa L.) bajo condiciones de riego - Sig Tu Meléndez, Aparicio Marcos (2019)
The present work was developed in the lands of Mr. Aparicio Sigtu Meléndez, located in the Hda. Hope, right. Los Beldacos, Canton Montalvo. The INIAP 14 variety was used as planting material. The treatments consisted of fungicides such as Ausoil in doses of 350 and 500 cc / ha; Pamona in doses of 400 and 600 cc / ha; Amistar top in doses of 350 and 500 cc / ha, plus an absolute witness. The experimental design proposed was Blocks Completely Random, with seven treatments and three repetitions. The comparisons of the averages were made using the Tukey test at 95% probability. The agricultural work that rice cultivation requires for its normal development such as land preparation, planting, weed control, phytosanitary control, irrigation, fertilization and harvesting were carried out. From the results obtained, it was determined that the diseases present in the rice crop during the development of the experiment were Rice blight (R. solani), Pod rot (S. oryzae), Helmintosporiosis (H. oryzae) and Burning (P oryzae); the absolute control treatment, without the application of fungicides, reported a higher incidence of the diseases in the evaluations carried out at 60 and 75 days after the transplant; in the variable severity, the highest percentage was recorded in the treatment that no fungicidal products were applied, therefore there is greater damage of the diseases to the Iniap 14 rice variety; In relation to the efficacy of fungicides, the Pamona product in doses of 400 and 600 cc / ha was more effective against the attack of Añublo del rice (R. solani) and Pod rot (S. oryzae); Ausoil in doses of 500 cc / ha was effective in the attack of Helmintosporiosis (H. oryzae) and Amistar top in doses of 350 cc / ha in the disease Burning (P. oryzae); The agronomic characteristics of plant height, tillers and panicles / m2, grains per panicle, weight of 1000 grains and yield were obtained by the application of Pamona in doses of 400 cc / ha and the greatest net benefit was for the use of Pamona in doses of 400 cc / ha with $ 216.77.